Tổng hợp oxit phức hợp perovskit La1-xSrxCoO3 kích thước nanomet bằng phương pháp sol-gel xitrat và nghiên cứu hoạt tính xúc tác của chúng - Minh Nguyệt, Trần Thị; Tráng, Nguyễn Công; Huấn, Nguyễn Quang; Quí, Nguyễn Minh; Chi, Trần Quế; Thai, Trần Doãn; Chân, Đỗ Thế; Trung, Nguyễn Quốc; Đăng, Lê Hải (Vietnam Journal of Chemistry, 2014)
Nanoparticle of Perovskite La1-xSrxCoO3(x = 0, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7) were prepared by using citric acid sol-gel method. The structure and morphology of products were investigated by X-ray difraction (XRD) and transmission electron microscopy (TEM). The specific surface area (BET) was determined by N2adsorption/desorption at 77 K. The catalytic oxidation of propene and removal NOx were studied by Temperature Program Surface Reaction (TPSR) over every compositions. The results show that the contened of substituted ion Sr2+ influenced on the oxidation temperature of propene